2019
DOI: 10.12669/pjms.35.5.720
|View full text |Cite
|
Sign up to set email alerts
|

Determining the caregivers’ burden in caregivers of patients with mental illness

Abstract: Objective: To examine the factors associated with caregivers’ burden in individuals providing care to family members suffering from serious mental illness. Methods: This Cross Sectional Study was carried out at Armed Forces Institute of Mental Health, Rawalpindi, from May 2015 to December 2015. A purposive sample of 120 family caregivers (60 males and 60 females, age range= 18-65) who were taking care of patients with serious mental illness (i.e. Major Depressive Disorder, Bipolar Disorder & Schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 11 publications
4
44
2
3
Order By: Relevance
“…The ZBI was validated in many countries across the world [54] and has recently been used in psychiatric clinical practice to assess the emotional burden in caregivers of patients affected by schizophrenia spectrum disorders [30,55]. A study, using ZBI, reported high level of burden associated with some caregiver variables (age, gender, educational level) and, at the same time, with the duration of both caregiving and schizophrenia [54].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ZBI was validated in many countries across the world [54] and has recently been used in psychiatric clinical practice to assess the emotional burden in caregivers of patients affected by schizophrenia spectrum disorders [30,55]. A study, using ZBI, reported high level of burden associated with some caregiver variables (age, gender, educational level) and, at the same time, with the duration of both caregiving and schizophrenia [54].…”
Section: Discussionmentioning
confidence: 99%
“…A study, using ZBI, reported high level of burden associated with some caregiver variables (age, gender, educational level) and, at the same time, with the duration of both caregiving and schizophrenia [54]. In particular, it was reported that caregivers who were married, less educated, living in rural areas and with low economic income normally provided longer period of support to their assisted individuals than others, often assuming an avoidant coping behaviour towards their assisted patients, which resulted in higher caregiver burden [30,55,56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 Furthermore, an interview with 10 and 6 families indicated a deficiency in the understanding of how to teach independence to patients leading to the poor desire to regularly take medication and subsequent relapse. 6 …”
Section: Introductionmentioning
confidence: 99%